Common pulmonary vein atresia: a case report and treatment experience sharing of a newborn diagnosed with common pulmonary vein atresia after two operations - Zhang, Kun; Tao, Shuguang; Gao, Wei; Gu, Jiangrong; Wen, Linlin; Fan, Yun (Frontiers in Pediatrics, 2025)
Common pulmonary vein atresia (CPVA) is a rare congenital heart disease characterized by the absence of functional connectivity between the pulmonary vein and any other heart cavity or systemic venous structure. A 13-h-old newborn (G3P3) was admitted to the department of pediatrics of a local maternity hospital and given tracheal intubation ventilator for assisted breathing due to systemic cyanosis, respiratory distress, and poor response 4 h after birth. He was transferred to Handan Maternal and Child Health Hospital 7 h after birth. After entering the department of neonatology, the child was considered to have anomalous pulmonary venous drainage (subcardiac type) after undergoing color Doppler examination. There was no obvious effect on the treatment, such as liquid replenishment and acid correction, so he was transferred to our hospital. After admission, respiratory failure complicated with heart failure, metabolic acidosis, and hyperlactatemia were initially diagnosed. After two-dimensional echocardiography, emergency surgery was decided after consideration of CPVA. Complete pulmonary venous malformation drainage and cardiopulmonary bypass-assisted repair were performed 9 h after admission. The patient was successfully discharged from the ICU on the 30th day after surgery, but on the 52nd day after surgery, pulmonary vein obstruction was found again. After emergency cardiopulmonary bypass-assisted repair, the pulmonary vein obstruction was corrected, but the child had multiorgan failure (MOF), coagulation function was abnormal, and vital signs were still difficult to maintain with cardiopulmonary bypass assistance after the second operation, and the family gave up treatment. Although we have made significant progress in understanding and processing CPVA, the early diagnosis, surgical treatment, and prognosis remain challenging. The changes in examination data we found in the evolution of the patient's condition during this period and the corresponding changes required constant alertness to the possibility of various problems, such as the occurrence of pulmonary vein obstruction and occlusion, and timely targeted treatment strategies. The treatment experience and lessons during this period can be referred to by everyone, hoping to provide some help in improving the treatment of CPVA patients.